Preface - Feige, Michael; Motzafi-Haller, Pnina (Hagar: Studies in Society and Culture, 2010)
Decades after Foucault’s prophetic words, the importance of space in social analysis has become commonplace within a variety of humanistic disciplines, leading to an exponential growth of research and theoretical deliberations.